2016
DOI: 10.3390/safety2010001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Passengers on All-Terrain Vehicle Crash Mechanisms and Injuries

Abstract: Traditional all-terrain vehicles (ATVs) are designed for single riders. Although carrying passengers is a known risk factor for injury, how passengers contribute to ATV crashes remains poorly understood. To address this question, we performed a retrospective chart review of ATV crash victims at a U.S. trauma center (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013). Of 537 cases, 20% were passengers or drivers with passengers. The odds of backward rollovers, falls/ejections, crashes on sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Riders are often injured when they are ejected or fall from the vehicle. Studies show that riders who fall/ are ejected to the side are at particular risk for extremity injuries and those who fall/are ejected to the rear are at greater risk for head injuries (Brandenburg et al, 2007;Jennissen and Denning, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Riders are often injured when they are ejected or fall from the vehicle. Studies show that riders who fall/ are ejected to the side are at particular risk for extremity injuries and those who fall/are ejected to the rear are at greater risk for head injuries (Brandenburg et al, 2007;Jennissen and Denning, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Independent risk factors that increase the likelihood of ORV-related deaths and injuries include roadway riding [9,11,12], being male and/or <16 years of age [13,14,32], youth operating adult-size ATVs [10], carrying passengers on ATVs designed for a single rider [9][10][11]33], alcohol [34][35][36], and lack of helmet use by ATV riders [34,[37][38][39]. Safety laws are designed to reduce crashes and injuries by focusing on risk factors, and Iowa's ORV laws and OHV park regulations do address some of these issues.…”
Section: Iowa Orv Law Enforcementmentioning
confidence: 99%
“…Passengers or operators with passengers are a significant proportion of crash victims, and roadway ATV-related fatalities are more likely to involve passengers than fatalities occurring off-road [9][10][11][12]42]. Almost all ATVs are designed for an operator only and passengers are an independent risk factor for ATV-related crashes and injuries [9,11,32].…”
Section: Carrying Passengersmentioning
confidence: 99%
“…Many authors have suggested methods to help prevent ATV-related crashes and decrease the morbidity and mortality from them when they do occur, including: (1) minimum age of 16 years for independent operation or mandatory parental supervision for those <16 years of age; (2) automobile driver's license or permit or educational classes with "hands-on" training; (3) head and eye protection during ATV operation; (4) abstention from alcohol and illicit drugs; (5) single operator only (i.e., no passengers); and (6) avoidance of public roadways [5,6,8,[11][12][13]30,31]. Similar efforts have been shown to reduce injury severity from motorcycles [32].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Multiple studies have outlined factors that increase the inherent risk associated with ATV use, including: no training or licensing requirement, ability to achieve high speeds (up to 65 mph), heavy weight (up to 600 lbs), lack of requirement for use of personal protection (e.g., helmets and goggles), use in areas with poor terrain, riding with passengers, and riding on roadways [5][6][7][8][9][10][11][12][13]. ATV-related injuries occur most commonly in males, in the age range late teens-early 20s, on weekends, in the evening, and during summer months.…”
Section: Introductionmentioning
confidence: 99%